Chariots and Other Wheeled Vehicles in Italy Before the Roman Empire - Crouwel, J. H. (Oxbow Books, 2012)
Chariots and Other Wheeled Vehicles in Italy before the Roman Empire presents evidence for transport by wheeled vehicle in Italy before the Roman Imperial period, the beginning of which is often thought to be marked by Augustuss conquest of Egypt in 30 BC. The study begins with a glossary of technical terms and with evidence for roads and the animals that were used in draught. The major part is concerned with the vehicles themselves - two-wheeled chariots and carts and four-wheeled wagons - their construction, the ways in which their draught animals were harnessed and controlled, and the uses